2013
DOI: 10.1148/radiol.13121631
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Type 2 Diabetes Mellitus: Changes in Tissue-specific Fat Distribution and Cardiac Function

Abstract: A 6-month exercise intervention in type 2 diabetes mellitus decreased hepatic TG content and visceral abdominal and paracardial fat volume, which are associated with increased cardiovascular risk, but cardiac function was unaffected. Tissue-specific exercise-induced changes in body fat distribution in type 2 diabetes mellitus were demonstrated in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 33 publications
(14 reference statements)
2
35
0
Order By: Relevance
“…In the study by Schrauwen-Hinderling et al (40), the 3-month combined endurance and strength training improved insulin sensitivity and the left ventricular ejection fraction but not MTC. Similarly, in the study by Jonker et al (21), no response was observed in MTC or epicardial fat after 6 months of endurance training in T2DM subjects, although hepatic TG content, visceral fat, and pericardial fat decreased. Overall, the data on the effects of exercise training on MTC are limited.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…In the study by Schrauwen-Hinderling et al (40), the 3-month combined endurance and strength training improved insulin sensitivity and the left ventricular ejection fraction but not MTC. Similarly, in the study by Jonker et al (21), no response was observed in MTC or epicardial fat after 6 months of endurance training in T2DM subjects, although hepatic TG content, visceral fat, and pericardial fat decreased. Overall, the data on the effects of exercise training on MTC are limited.…”
supporting
confidence: 56%
“…In previous long-term moderate-intensity training studies, epicardial fat has shown a decrease of 9% (23) and pericardial fat a decrease of 20% (21). As the present training intervention was shorter than used in the previous studies, we assumed that the training response would be at a level of 5% per unit (assuming the SD to be 10% per unit).…”
Section: Methodsmentioning
confidence: 91%
“…However, in type 2 diabetes patients and impaired glucose-tolerant subjects, the effects of exercise training on IMCL content are less consistent. Although some studies report augmented IMCL storage upon exercise training (Meex et al, 2010;Peters et al, 2012), others have reported no change (Jonker et al, 2013) or a reduction (Bruce et al, 2004;Solomon et al, 2008). Although these apparent differences may originate from different training protocols, they might also be a reflection of the limited exercise capacity of patients with type 2 diabetes (Stephens and Sparks, 2015).…”
Section: Long-term Exercise Training Effectsmentioning
confidence: 99%
“…Pericardial fat quantification As described before [12], to quantify the pericardial fat volume, the heart was imaged using electrocardiographicallygated breath-holds with a multi shot turbo spin echo sequence in a four-chamber view orientation. Water was suppressed using SPIR.…”
Section: Mr Protocolmentioning
confidence: 99%